Attending to the social–political dimensions of urban flooding in decision‐support research: A synthesis of contemporary empirical cases. (25th October 2021) - Eakin, Hallie C.; Parajuli, Jagadish; Hernández Aguilar, Bertha; Yogya, Yamini
Abstract: Public adaptation decision‐making entails a negotiation of disparate perspectives on risk, harm, and value in relation to understanding impacts, as well as in choosing among alternative adaptation strategies. Public adaptation decisions impact the distribution of resources and risk and thus, while not always acknowledged, such decisions are inherently social and political, with implications for equity and justice. We synthesize insights from 128 empirical case studies of processes of public decision‐making pertaining to infrastructural flood risk adaptation in urban areas. We focus on urban flood risk adaptation efforts because of the growing threat of flooding in urban areas globally, the technical orientation of such investments and the social equity issues associated with urban flood exposure and response. We explore the assumptions about the decision criteria and decision‐support needs presented in this research. And we document the extent to which these studies incorporate sources of knowledge on the social dimensions of flood impacts, consider social and political criteria in evaluating intervention strategies and account for issues of equity and justice in the adaptation process. We conclude with a discussion on the potential obstacles in the research community for deeper engagement with the social and political dimensions of adaptation decision support, and ways to address such obstacles. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : Knowledge contributions and approaches to enhance integration of socio‐political concerns into different phases of urban flood adaptation decision processes.